An Exploration of Family Members’ Roles in the Context of Breast Cancer: A Narrative Study in Malaysia - Wan Mamat, Wan Hasliza; Jarrett, Nikki; Lund, Susi (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Breast cancer is a significant health problem that affects patients and their family members. Family members are often key to supporting the patient. However, there is an inadequate understanding of the role of female breast cancer patients’ family members in Malaysia. This study aimed to explore the roles of family members of female breast cancer patients from symptom appraisal until the patient treatment commences. Methods: Snowball sampling was applied and 14 participants were recruited through the nomination of the female breast cancer patients. The participants took part in in-depth, face-to-face, and audio-recorded one-time interviews. All of the interviews were subsequently transcribed verbatim and analysed using narrative analysis. Results: Five themes were identified with regard to the roles of family members: 1) confirming breast changes; 2) managing personal emotions; 3) seeking the information; 4) seeking alternative forms of treatment; and 5) advocating for conventional treatment. Conclusion: This study discovered that family members play an important role in the journey of women with breast cancer from the time an abnormality is discovered to the time the patient receives treatment. During this time, many of them suppressed their emotions in order to focus on the women suffering from breast cancer. Healthcare professionals working with breast cancer should recognise and support the key role of family members in supporting women to get treatment. It is important to take a proactive approach in recognising the early signs of stress for family members and, when appropriate, offering them additional sources of support.